Sensing CA 15-3 in point-of-care by electropolymerizing O-phenylenediamine (oPDA) on Au-screen printed electrodes - Gomes, Rui S. (PLoS One, 2018)
This work presents an alternative device for cancer screening in liquid biopsies. It combines a biomimetic film (i) with electrochemical detection (ii). The biomimetic film (i) was obtained by electro-polymerizing amine-substituted benzene rings around a CA 15–3 target. This protein target was previously adsorbed on a gold (Au) support and incubated in charged monomers (4-Styrenesulfonate sodium and 3-Hydroxytyraminium chloride). The protein was further eliminated by enzymatic activity, leaving behind vacant sites for subsequent rebinding. Electrochemical detection (ii) was achieved on an Au working electrode, designed on commercial screen-printed electrodes. Raman spectroscopy, atomic force microscopy and ellipsometric readings were used to follow the chemical modification of the Au surface. The ability of the material to rebind CA15-3 was monitored by electrochemical techniques. The device displayed linear responses to CA15-3 ranging from 0.25 to 10.00 U/mL, with detection limits of 0.05 U/mL. Accurate results were obtained by applying the sensor to the analysis of CA15-3 in PBS buffer and in serum samples. This biosensing device displayed successful features for the detection of CA 15–3 and constitutes a promising tool for breast cancer screening procedures in point-of-care applications. Moreover, its scale-up seems feasible as it contains a plastic antibody assembled in situ, in less than 1 minute, and the analysis of serum takes less than 30 minutes.